Beyond propaganda, aestheticism and commercialism - Wu, Jing (Javnost (Ljubljana), 2007)
The paper traces the development of documentary photography in modern China through case studies of photographers and their work in different periods of history. It argues that technological potential, social conditions and cultural values work together to enable and condition the development of specific styles of photography. The coming of age of documentary photography as an independent way of observing society and intervening in social change inChina is the result of overcoming three institutional influences of art: propaganda, aestheticism and commercialism. The future development of this artform depends on its continued negotiation with these three institutional forces and its ability to remain relevant to social processes.
Keywords: Kitajska; dokumentarna fotografija; fotografski motivi; družbene razmere; družbene spremembe; politične razmere